Fraud Management Model and Forensic Accounting – A Systematic Literature Review - Firmansyah, Deri; Suryana, Asep; Susetyo, Dwinanto Priyo; Syafei, M. Yani (International Journal of Business, Law, and Education, 2024)
This study interprets the importance of critical thinking and concern for the triggers of fraudulent behavior and financial fraud. The purpose of the study is expanded by explaining the application of fraud management as corporate governance to prevent fraud, and the involvement of forensic accounting practices is necessary. This study, a systematic literature review (SLR) by adopting part of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method, to identify, and construct a fraud management and forensic accounting model. The findings, fraudulent behavior occurs because there is a triggering factor, and someone has difficulty ignoring it. Psychologically it has taken root and rationalized the truth of fraud on the basis of pressure, opportunity supported by capability, such as triggers for fraudulent behavior in the fraud triangle model and the diamond fraud model. Synthesis of findings, it is important for internal control in fraud management to be applied for early detection and investigation and it is necessary to involve forensic accounting practices to detect, investigate accounting and litigation to resolve financial fraud in the financial data-based justice system. The novelty of this research offers a fraud management and forensic accounting model to prevent fraud and the financial condition of the company.